Unit Kenal Diri: Solutions to overcome student character problems post-pandemic at SMK Muhammadiyah 3 Wates - Zahro Varisna Rohmadani; Dwi Sri Handayani; Agustina Rahmawati (Community Empowerment, 2024)
Post Covid-19 pandemic, there has been a shift in student behavior at SMK Muhammadiyah 3 Wates, including an increase in smoking behavior, recorded at 74.6%, and reproductive health issues such as premarital sex. This highlights the need to initiate school programs that can address student character issues. Community service was conducted through an initiation program to establish a Self-Awareness Unit (UKD), with the aim of increasing student knowledge about the dangers of smoking and the prevention of premarital sex, as well as preparing teachers and students as UKD cadres. The community service implementation method included health screening training for teachers and students acting as UKD cadres, and health education to prevent smoking and premarital sex. In addition, an introduction to the role and function of the UKD was conducted as a forum to increase students' self-awareness regarding the importance of consultations on character, interests, talents, and personal health. The results of the community service showed a significant increase in the understanding and skills of teachers and school cadres in conducting health screening. After the training, 87.55% of participants showed an increase in knowledge about the dangers and prevention of smoking and premarital sex.